Diskriminasi Gender Akibat MinimnyaPengetahuan Kesetaraan Gender Di Kalangan Masyarakat - Marisa Putri; Efti Restiana; Dwi Putri Lestarika (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Gender discrimination is still a significant issue in many countries, including Indonesia. This trend is caused by a variety of factors, the most notable of which being the general public's lack of knowledge on gender equality. The purpose of this article is to examine how much knowledge about gender equality contributes to gender discrimination in the general population. Using literature and research, this article will examine gender discrimination, its causes, and the impact of a lack of understanding of gender in various aspects of life. The findings of the study indicate that increasing public understanding of gender equality can have a significant impact on reducing discrimination.